PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL BERDASARKAN KONVENSI PARIS DAN PERJANJIAN TRIPS SERTA PENERAPANNYA BERDASARKAN UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK - Sari D, Siti Nurul Intan (Jurnal Yuridis, 2015)
Marks is a sign in the form of images, names, words, letters, numbers, color composition, or a combination of these elements, having distinguishing features and used in the trading of goods or services. Marks can be divided into three types based on reputation and renown of a marks, namely: normal marks, well-known marks and famous marks. In the business world, many once we find well-known marks that come from outside and within the country. The need to protect well-known marks becomes very important, in the face of the violations that occurred in the trade of goods and services. Protection well-known marks is needed to avoid loss of mark holders and consumer  users  of  goods  and  services.  In  this  paper,  the  problem  :  What  is law protection of well-known marks based on the Paris Convention and the Trips Agreement and the application pursuant to Law No. 15 of 2001 on Marks? Legal Protection for well-known marks can be attributed to the Paris Convention, Trips Agreement and Law No. 15 of 2001 on Marks.